A comparison of suturing technique for repair of episiotomy : a randomised control trial of Malay primigravidae in Hospital Universiti Sains Malaysia, Kota Bharu, Kelantan, Malaysia 2005 - 2006 - Ishak, Maizun (2006)
OBJECTIVE : To determine the outcome of episiotomy repair between 2 suturing techniques - continuous subcuticular technique and transcutaneus interrupted technique among Malay primigravida. METHODOLOGY : A 6 months prospective randomized study over a total of 200 Malay primigravida in Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan, who had spontaneous vaginal delivery (SVD) from August 2005 till January 2006. This study was conducted to compare the outcome of two suturing techniques - continuous subcuticular technique and transcutaneous interrupted technique. The outcome measured were perineal pain at 24 hours, 10 days and 3 months and also dyspareunia after 3 months post-delivery. RESULTS : A total of 200 patients ( 100%) were able to be reviewed at 24 hours, 148 patients (74%) at day 10 and 131 patients (65.5%) were reviewed at 3 months postdelivery. There was significantly less time taken to repair episiotomy in subcuticular continuous technique compared with transcutaneous interrupted technique ( 17.2 min vs 24.8 min, p<0.05). However, there was no significant difference in perineal pain score at 24 hours (2.4 vs 2.3, p=0.674), 10 days (2.3 vs 2.6, p=0.361) and 3 months (1.3 vs 1.3, p=0.728) post-delivery. There was no difference in dyspareunia at 3 months post-delivery review in both groups (p=0.331). The perineal pain at 24 hours was significantly correlated with episiotomy length after repaired (r: -0.185, p=0.009). However, there was no significant difference in pain on ambulation at 24 hours (p=0.487) and 10 days (p=0.712), use of analgesia at 24 hours (p= 0.841), 10 days (p= 0.909) and 3 months (p= 0.334) post-delivery. There was no difference in urinary or bowel problems for both groups at 24 hours and 10 days (p > 0.05). There was no statistically significant difference in wound morbidity of both group studied at 24 hours and 10 days postdelivery (p > 0.05) CONCLUSION: Subcuticular continuous technique should be given as an option when repairing an episiotomy. Even though there was no reduction in the symptoms of perineal pain and dyspareunia, this method significantly required less repairing time.